(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
Remote sensing and Geographic Information Systems (GIS) are essential tools in determining the spatiotemporal extent of Landuse, and Land Cover (LULC) changes, as well as a variety of individual concerns, such as annual and seasonal changes in LULC caused by human interferences and interactions between the physical environment, cultural context, and anthropogenic factors. This study focuses on the LULC change of Sonadia Island, and it uses multi-temporal Landsat imagery from 1990 through 2020. The output analysis revealed four sub-features: mudflats, vegetation, open space, and water bodies. Vegetation cover decreased from 1486.71 hectares in 1990 to 986.13 hectares in 2000, and in 2020, the total area covered by vegetation increased significantly, reaching 1186.47 hectares, up from 497.97 hectares in 2010. Open space increased from 317.16 hectares in 1990 to 510.75 hectares in 2000. The net area expanded to 631.98 hectares in 2010 and then lost to 421.29 hectares in 2020. There was a consistent increase in the mudflats section from 1990 to 2010, when the amounts were 491.4 and 1179 hectares, respectively. By 2020, the area extent decreased to 796.41 hectares. From 1990 to 2000, the waterbody declined from 305.46 to 262.17 hectares, then slightly increased to 291.78 hectares in 2010, and then shrank again to 196.56 hectares in 2020. Therefore, this study could help policymakers decide on future landscape planning and evaluate Sonadia Island’s current condition for long-term coastal management. J. Asiat. Soc. Bangladesh, Sci. 49(2): 139-148, December 2023